Landscape, emblematic commemoration, and identity: La Pampa de Ayacucho, as "geography of memory" - Oré Medina, Juan José (2021)
The article reflects, from a geographic perspective, the emblematic commemoration landscape of the Pampa of Ayacucho, as place. Go into at the same time, the political reasons of the because the Peruvian Estado, the good marks community of Ayacucho, it had decision from where and how to locate the Obelisco in homage to the conquerors of Ayacucho's battle of 1824. Finally, the relations among geography and room are presented by heart and identity, affecting of as the society ayacuchana, notify of the rituals, civic ceremonies, annually; Considering point the space and to the monument, as cultural and symbolic practices that they inculcate them the adhesion sentiment and loyalty toward his national heroes to